2005
DOI: 10.1892/0891-6640(2005)19[683:eooaoa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Administration of a Commercial Activated Charcoal Suspension on Serum Osmolality and Lactate Concentration in the Dog

Abstract: The purpose of this investigation was to determine the effects of an activated charcoal (AC) suspension containing propylene glycol and glycerol on serum osmolality, osmolal gap, and lactate concentration in dogs. Six healthy adult dogs were administered 4 g/kg AC in a commercially available suspension that contained propylene glycol and glycerol as vehicles. Blood samples were taken before and 1, 4, 6, 8, 12, and 24 hours after the administration of the test suspension. Samples were analyzed for osmolality, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 8 publications
(14 reference statements)
0
19
0
Order By: Relevance
“…The reference value for osmolality in the dog has been reported to be 301, 7 311, 8 309, 9 and 303 mOsm/kg 10 . These studies reported results as a pretreatment value before measuring the effects of another intervention on osmolality.…”
Section: Introductionmentioning
confidence: 99%
“…The reference value for osmolality in the dog has been reported to be 301, 7 311, 8 309, 9 and 303 mOsm/kg 10 . These studies reported results as a pretreatment value before measuring the effects of another intervention on osmolality.…”
Section: Introductionmentioning
confidence: 99%
“…4 Samples were also evaluated for acid-base status and concentrations of sodium, potassium, blood urea nitrogen (BUN), and glucose. 4 Samples were also evaluated for acid-base status and concentrations of sodium, potassium, blood urea nitrogen (BUN), and glucose.…”
Section: Box 74-2 Appropriate Indications and Contraindications To Inmentioning
confidence: 99%
“…4 Samples were also evaluated for acid-base status and concentrations of sodium, potassium, blood urea nitrogen (BUN), and glucose. 4 All six dogs drank frequently after AC administration, but water intake or urine output was not recorded. 4 In this study, mean serum osmolality, osmolal gap, and lactate concentration were significantly increased after suspension administration compared with baseline, typically increasing at 1 hour after AC administration, peaking at 4 hours, and returning to baseline by 24 hours.…”
Section: Box 74-2 Appropriate Indications and Contraindications To Inmentioning
confidence: 99%
See 2 more Smart Citations